2013
DOI: 10.5935/1808-8694.20130006
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term impact of adenotonsillectomy on the immune system

Abstract: This study indicated that adenotonsillectomy does not pose negative short or long term impacts upon the cellular and humoral immunity of children submitted to the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…1B ), with predominance among the benchmarks. Our findings, however, are similar to those found by Santos et al, 9 who reported normal levels in the preoperative and postoperative periods (1 to 2 months). However, after 12 months of follow-up, the IgA and IgG levels showed significant increases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…1B ), with predominance among the benchmarks. Our findings, however, are similar to those found by Santos et al, 9 who reported normal levels in the preoperative and postoperative periods (1 to 2 months). However, after 12 months of follow-up, the IgA and IgG levels showed significant increases.…”
Section: Discussionsupporting
confidence: 92%
“…It is associated with improved quality of life and sleep, although its causes and its effects on the immune system (e.g., reducing infections) are still controversial. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the largest components of Waldeyer ring, [24] they are secondary lymphoid organs, and part of the mucosa-associated lymphoid tissue. [5,6]…”
Section: Introductionmentioning
confidence: 99%